Parenting concern in the pre-Islamic poetry - دعدع رندة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This study is to reveal a new idea has not been equally thorough lesson and research, and opens a wide range of reading poetry ignorant new reading, in response to Jeddah idea of ​​fatherhood, which provides a great opportunity for tracers humanitarian depths, Thighs in this hair, is to Atef paternity, which in if you feel concerned about the children of the exhaust ever and the fates of time, and the approach of death, and the positions of the mainland and disobedience alike. The research on reading concern paternity in pre-Islamic poetry, in light of the text taken from a study of poetic text components, a way to express the same poet (father) plying under the weight of a sense of deep concern.